Association of whole grain, refined grain, and cereal consumption with gastric cancer risk: A meta‐analysis of observational studies. Issue 1 (11th November 2018) - Xu, Yujie; Yang, Jie; Du, Liang; Li, Ka; Zhou, Yong
Abstract: Many studies have analyzed the relationship between cereal, whole, or refined grain and the risk of gastric cancer (GC) and have yielded mixed results. Therefore, we performed a meta‐analysis of observational studies to summarize the available evidence on this topic. Databases such as PubMed, EMBASE, Web of Science, MEDLINE, and the Cochrane Library were searched for studies focusing on these associations from inception to October 2017. Summary odd ratios (OR) and 95% confidence intervals (CI) were calculated by using either a random‐ or fixed‐effect model according to the between‐studies heterogeneity. Subgroup analysis was also performed. In total, eleven studies that included 530, 176 participants were identified. In a pooled analysis of all studies, cereal exposure was not associated with GC risk (OR, 1.11, 95%CI, 0.85–1.36). Specific analyses indicated that whole grain consumption was associated with decreased GC risk (OR, 0.61, 95%CI, 0.40–0.83) and that refined grain consumption was associated with increased GC risk (OR, 1.65, 95%CI, 1.36–1.94). Higher whole grain and lower refined grain intake but not cereal consumption reduces GC risk. This study has been registered at ClinicalTrials.gov (ID: NCT03419663). Abstract : In this work, we identified eleven articles which included 530, 176 individuals from United States, Italy, China, Spain, Poland, Mexico, Uruguay and European countries, and found statistically significant inverse association between whole grain consumption and gastric cancer (GC), positive association between refined grain consumption and GC and no association between overall cereal consumption and GC.